Selected Papers on Accounting, Auditing and Professional Problems/Edward Stamp: Later Papers. - Zeff, Stephen A.; Autrey, Herbert S. (The Accounting Review, 1990)
Reviews the books "Selected Papers on Accounting, Auditing and Professional Problems," by Edward Stamp and "Edward Stamp: Later Papers," edited by Michael J. Mumford.